Absence of both Sos-1 and Sos-2 in peripheral CD4(+) T cells leads to PI3K pathway activation and defects in migration - Guittard, Geoffrey (Eur J Immunol, 2015)
Sos-1 and Sos-2 are ubiquitously expressed Ras-Guanine Exchange Factors involved in Erk-MAP kinase pathway activation. Using mice lacking genes encoding Sos-1 and Sos-2, we evaluated the role of these proteins in peripheral T-cell signaling and function. Our results confirmed that TCR-mediated Erk activation in peripheral CD4(+) T cells does not depend on Sos-1 and Sos-2, although IL-2-mediated Erk activation does. Unexpectedly, however, we show an increase in AKT phosphorylation in Sos-1/2dKO CD4(+) T cells upon TCR and IL-2 stimulation. Activation of AKT was likely a consequence of increased recruitment of PI3K to Grb2 upon TCR and/or IL-2 stimulation in Sos-1/2dKO CD4(+) T cells. The increased activity of the PI3K/AKT pathway led to downregulation of the surface receptor CD62L in Sos-1/2dKO T cells and a subsequent impairment in T-cell migration.